USE OF MOBILE-ASSISTED LANGUAGE LEARNING (MALL) THROUGH THE HELLOTALK APPLICATION IN IMPROVING SPEAKING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Siti Melasari; Diana Rosa Agustina; Siti Mala Nurfayyisa; Naf’an Tarihoran (Adisam Publisher, 2025)
The rapid development of mobile technology has encouraged with Mobile Assisted Language Learning (MALL) in language education, particularly for improving speaking skills. This systematic literature review aims to analyze how the HelloTalk app is used to improve learners' speaking skills and identify its educational potential in a MALL environment. The method used is a qualitative systematic review, in which empirical studies published between 2020 and 2025 were collected from several academic databases and selected based on predetermined inclusion criteria. Various databases, such as Mendeley, Scopus, ScienceDirect, PubMed, ERIC, and Google Scholar. The results indicate that HelloTalk helps establish authentic communication, increases learners' speaking confidence, and provides meaningful interactions with native or experienced speakers through features such as voice messages, audio calls, and immediate feedback. Several studies have also found that using HelloTalk increases learners' motivation and reduces fear of speaking, especially in collaborative communication. In conclusion, the use of HelloTalk in MALL has highly beneficial outcomes for the development of speaking skills. This study suggests that educators should consider integrating mobile-based social interaction platforms into language learning, as They provide opportunities for students to continually practice speaking in real-life ways outside of the classroom environment.